The associations between single nucleotide polymorphisms and diabetic retinopathy risk: an umbrella review - Shaofen Huang; Yonghui Feng; Ying Sun; Jiazi Liu; Pu Wang; Jingrong Yu; Xin Su; Shasha Han; Shiqi Huang; Haokun Huang; Shiyun Chen; Ying Xu; et al. (Endocrine Journal)
This umbrella review was conducted aiming to assess the association between genetic variations and the development of diabetic retinopathy (DR) by collecting and evaluating available systematic reviews and meta-analysis results. We evaluated the methodological quality using the Measurement Tool to Assess Systematic Reviews (AMSTAR) 2.0, estimated the summary effect size by using the random effects model and calculated the 95% prediction intervals (PIs). Evidence from the included meta-analyses was graded according to established criteria as follows: convincing, highly suggestive, suggestive, weak, or not significant. This umbrella review included 32 meta-analyses of 52 candidate SNPs. The 12 selected meta-analyses were rated as “high,” 2 studies were rated as “moderate,” 11 studies were graded as “low,” and the remaining 7 studies were graded as “critically low” in terms of methodological quality. Carriers of specific genotypes and alleles of the transcription Factor 7-like 2 C/T (TCF7L2 C/T) polymorphism (rs7903146, p < 0.001) might be more susceptible to the occurrence of DR in the homozygous and recessive models, and these associations were supported by “convincing” evidence. Significant associations were also found between interleukin-6 (IL-6) -174 G/C (rs1800795; p < 0.05) or vascular endothelial growth factor (VEGF) polymorphisms (rs2010963, rs699947, rs1570360, rs2010963, rs699947, rs2146323; all p values <0.05) and DR risk, but these associations were supported by “weak” evidence. The TCF7L2 C/T variant could be identified as a definitive genetic risk factor for the development and progression of DR. Data from additional in-depth studies are needed to establish robust evidence for the associations between polymorphisms of IL-6 or VEGF and DR.